2014
DOI: 10.1002/asia.201402954
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Reduction of Mononuclear High‐Spin Iron(III) Complexes to Mononuclear Low‐Spin Iron(II) Complexes in Aqueous Media and Nuclease Activity via Self‐Activation

Abstract: Mononuclear high-spin [Fe(III) (Pyimpy)Cl3 ]⋅2 CH2 Cl2 (1⋅2 CH2 Cl2 ) and [Fe(III) (Me-Pyimpy)Cl3 ] (2), as well as low-spin Fe(II) (Pyimpy)2 ](ClO4 )2 (3) and [Fe(II) (Me-Pyimpy)2 ](ClO4 )2 (4) complexes of tridentate ligands Pyimpy and Me-Pyimpy have been synthesized and characterized by analytical techniques, spectral, and X-ray structural analyses. We observed an important type of conversion and associated spontaneous reduction of mono-chelated high-spin Fe(III) (1⋅2 CH2 Cl2 and 2) complexes to low-spin bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 68 publications
0
12
1
Order By: Relevance
“…For complexes 1 to 4, magnetic moments were found to be 5.31, 5.49, 5.59, 5.85BM respectively, that is predicting the stabilization of high-spin d 5 iron(III) centre in all complexes, it is consistent with the magnetic moment reported in literature. [47] (See supporting information S14−S17). Thermal stability of all the complexes was determined using TGA analysis.…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
“…For complexes 1 to 4, magnetic moments were found to be 5.31, 5.49, 5.59, 5.85BM respectively, that is predicting the stabilization of high-spin d 5 iron(III) centre in all complexes, it is consistent with the magnetic moment reported in literature. [47] (See supporting information S14−S17). Thermal stability of all the complexes was determined using TGA analysis.…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
“…The Fe–N im bond distances are 1.875 Å (Fe1—N3) and 1.912 Å Fe1—N7 and Fe–N py distances have been found to have slight differences 2.031 Å (Fe1—N8), 2.031 Å (Fe1‐N5), 2.093 Å (Fe1‐N4), 2.122 Å (Fe1‐N1). A similar pattern was observed in case of complex 2 (minor differences in N py distances) N py distances were found consistent with the data reported in the literature, however the N im distances were shorter in our case as compared to the reported values. The bond parameters for complexes 1 and 2 were quite similar to the data obtained from theoretically optimized geometries of both the complexes (shown in Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported iron complex derived from meridional tridentate ligand (L Ph ) having NNN donors (Shown in Scheme ) . Addition of H 2 O 2 to this complex did not provide us the indication of generation of stable hydroperoxo and oxo species in solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous reduction of the Fe III under aerobic conditions is quite rare in iron coordination chemistry. A few examples of the spontaneous reduction of a ferric ion chelated with bis(methylimidazolyl)ketone, salicyloyl hydrazonodithiolane, hydrazide, or Schiff base ligands have been identified in the literature, but the mechanism of the reduction has not been reported. Nevertheless, Sosa‐Torres et al reported that oxidative dehydrogenation of polyamine ligands in the presence of Fe III led to the Fe II complexes of the corresponding imine ligands , .…”
Section: Resultsmentioning
confidence: 99%